Repeated Copulation and Guarding, and Their Relationship With Male and Female Morphological Traits in the Water Scorpion Nepa hoffmanni - Hyoseul Hyun; Byeongho Lee; Chang S. Han (Ecology and Evolution, 2024)
ABSTRACT Insects copulate multiple times not only with different mates but also with the same mate, which is called repeated copulation. It occurs as a repeated alternation between copulation and mate‐guarding, leading to the prolonged physical attachment between males and females. Particularly, in species where males forcefully grasp females, attempt to mate without courtship and exhibit repeated copulations, male and female morphological traits are expected to be associated with mating characteristics. In this study, we describe for the first time the detailed mating behaviour and patterns of repeated copulations in the water scorpion Nepa hoffmanni (Nepidae, Hemiptera). Nepa hoffmanni repeated copulation and guarding approximately 10 times on average. Over repeated copulations, copulation duration decreased while guarding duration increased, potentially due to decreased male sperm reserves and increased female mating reluctance. Additionally, we found that average guarding duration was positively associated with male leg length and negatively associated with female leg length. This suggests that shorter male legs may enhance courtship efficiency or intensity, while shorter female legs may be less effective at resisting male mating attempts, leading to a quicker initiation of subsequent copulations with the same partner. This indicates that the evolution of repeated copulations may be linked to the evolution of morphological characteristics. Therefore, our study provides novel insights into the evolution of the mating behaviour of water scorpions.